Secrecy and concealment: studies in the history of mediterranean and Near Eastern religions - Kippenberg, Hans Gerhard; Sṭrumzah, Gedalyahu Gʹ. (Studies in the history of religions, 1995)
This volume deals with secrecy and concealment in the history of mediterranean religions as pattern of social interaction. Secrecy is a powerful means in establishing identity and interaction as G. Simmel has demonstrated. Using his approach the scholars of this volume describe and explain the practical meaning of concealment in two different religious systems: in Egyptian and Greek polytheism and in Jewish, Christian, Gnostic and Shi'i monotheisms. This point of view reveals that all these religions shaped social norms concerning public and private aspects of the human self.
Proceedings of a meeting held June 1-4, 1993, at the Werner Reimers-Stiftung, Bad Homburg, Germany
Includes bibliographical references and index
Keywords: Mediterranean Region -- Religion -- Congresses; Middle East -- Religion -- Congresses; Naher Osten; Mittlerer Osten; Nordafrika; Mittelmeerraum; Konferenzschrift -- 1993 -- Homburg, Höhe; Geheimnis; Kippenberg, Hans Gerhard; Geschichte; Monotheismus; Polytheismus